2021
DOI: 10.1186/s12885-021-08398-z
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colo-rectal cancer: real life experience from an Indian tertiary care center

Abstract: Background No data exist for the long-term outcome of metastatic colorectal cancer (mCRC) from the Southern part of Asia. The primary objective of the study is to evaluate the survival outcome of mCRC from an Indian tertiary care center. The study also aims to highlight the treatment pattern practiced and the unique clinico-pathologic characteristics. Methods This is a single-center retrospective observational study done at a large referral tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
4
7
0
Order By: Relevance
“…The same study and several other authors have also reported a mean age of less than 50 years in Indian patients with CRC [11][12][13]. The CRC in the younger population is considered to be generally more aggressive and to have a higher chance of recurrence [14,15]. However, in this cohort, the EOCRC does not have a worse outcome.…”
Section: Discussionsupporting
confidence: 58%
“…The same study and several other authors have also reported a mean age of less than 50 years in Indian patients with CRC [11][12][13]. The CRC in the younger population is considered to be generally more aggressive and to have a higher chance of recurrence [14,15]. However, in this cohort, the EOCRC does not have a worse outcome.…”
Section: Discussionsupporting
confidence: 58%
“…PRISMA, Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Sharma et al, 2021;Tabchouri et al, 2021;Yang et al, 2021;Zhou et al, 2021;Flood et al, 2022;Iwasaki et al, 2022;McCleary et al, 2022;Meyer et al, 2022;Nagao et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine papers were excluded from the review for age-related reasons: six studies had 0–3 patients under age 50. Forty-three studies included patients under age 50 but did not present results stratified by age or did not stratify using an age ≤50 years old for stratification; one study provided above/below-age data but failed to include symbols (≥ or ≤) or descriptive text to indicate which group included the cutoff age (Sternberg et al , 1994; Nakae et al , 1995; Nakamura et al , 1999; Akasu et al , 2000; el-Ghazawy et al , 2001; Luna-Pérez et al , 2002; Al-Shamsi et al , 2003; Kanemitsu et al , 2003; Carmignani et al , 2004; Lloyd et al , 2006; Nervi et al , 2006; Lawson et al , 2008; Sobhani et al , 2008; Song et al , 2009; Aghili et al , 2010; Lemmens et al , 2011; Sjo et al , 2011; Lieu et al ., 2014; Park et al , 2014; Saluja et al , 2014; Adachi et al , 2015; Lam et al , 2015; Sica et al , 2015; Simkens et al , 2015; 2016; Maillet et al , 2016; Wang et al , 2016; Cicero et al , 2017; Hojo et al , 2017; Patil et al , 2017; Cigdem Arslan et al , 2018; Kondo et al , 2021; Melli et al , 2021; Rieser et al , 2021a, 2021b; Sharma et al , 2021; Tabchouri et al , 2021; Yang et al , 2021; Zhou et al , 2021; Flood et al , 2022; Iwasaki et al , 2022; McCleary et al , 2022; Meyer et al , 2022; Nagao et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…With the availability of effective chemotherapy and access to a variety of ablative and non-surgical modalities of LDTs, an increasing number of patients with CRLM are being managed through a combination of the different treatment modalities ( 17 , 18 ). Though the multimodality approach has become an integral part of treating CRLM, literature exploring multimodality treatment outcomes is limited especially from the South Asian region ( 11 , 12 , 19 22 ). This is the largest series on multimodality liver-directed therapy in CRLM from the Indian sub-continent.…”
Section: Discussionmentioning
confidence: 99%
“…India has a low incidence of CRC compared to the West, but with the increasing availability of diagnostic modalities, an increasing number of cases are being detected ( 10 ). The available literature on CRLM from India and South Asia is extremely scarce, and available studies do not focus on the management of CRLM ( 11 , 12 ). This is one of the earliest experiences from South Asia highlighting the multidisciplinary management of CRLM and the oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%